Acedía, aegritudo, depresión: modernidad de un poeta medieval - Santagata, Marco (Cuadernos de Filología Italiana, 2005)
In opposition to the courtesan liric, Petrach’s poetry is not characterized by a dialogic and social dimension. It does not have the loved as its center, but the poet himself, and its fundamentally subj ective. Taking this interpretation as a point of departure, the author analises sonnet n. 272, which is considered extremely modern as far as some symptoms of what is actually called a depression can be discovered in it. Texts extracted from his S e c retum seem to confirm this intuition about Petrach’s complex psicology.